SEMINAR IDENTIFIKASI BAKTERI ESCHERICHIA COLI O157:H7 PADA FESES PENDERITA DIARE DENGAN METODE KULTUR DAN PCR - Vincentia Ade Rizky; Sa'adah Siregar; Visensius Krisdianilo; Asvia Rahayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The technique of identifying Escherichia coli O157: H7 bacteria in the feces of diarrhea sufferers using a molecular method, namely PCR has been proven to be more sensitive and shows fast results but is expensive when compared to conventional methods. Therefore, it can be recommended and used by health workers in early detection so that it will help make the diagnosis faster and determine treatment more effectively. The results of this seminar aim to make it easier for laboratory staff to identify the Escherichia coli O157: H7 bacteria in diarrhea sufferers.